1988
DOI: 10.1038/jcbfm.1988.34
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Flow and Rate Constants in a Kinetic Model of [99mTc]-Hexamethyl-Propylene Amine Oxime in the Human Brain

Abstract: Summary:The values for flow and rate constants for a kinetic model of [99mTc]-hexamethylpropyleneamine ox ime (HM-PAO) distribution in the human brain were de termined. The single-pass extraction ratio of HM-PAO was also determined in the rat brain by the indicator dif fusion method; a value of 0.90 ± 0.02 (mean ± SEM, n = 5) was obtained. Time course data of brain activity and arterial blood activity of the tracer were fitted to a four compartment model: Values of blood flow and the first order rate constants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…Higher values may be expected for white matter due to the high content of lipids in these regions. This is suggested by the studies of Matsuda et al (1988). In this context, it should be noted that the bolus injection experiments analyzed here are weighted towards the gray matter of the brain since it receives about 80% of the bolus (Ing var et al, 1965).…”
Section: The Modelmentioning
confidence: 84%
See 2 more Smart Citations
“…Higher values may be expected for white matter due to the high content of lipids in these regions. This is suggested by the studies of Matsuda et al (1988). In this context, it should be noted that the bolus injection experiments analyzed here are weighted towards the gray matter of the brain since it receives about 80% of the bolus (Ing var et al, 1965).…”
Section: The Modelmentioning
confidence: 84%
“…Therefore, as in the case when calculating the flow of whole brain (Andersen et aI., 1988c), one must measure not only Cj and A, but also Rj, in order to calculate the regional flow Fj in absolute units of mllg/min. Matsuda et al (1988) proposed to determine the local retention Fj using serial SPECT imaging as well as sampling of arterial blood. They assumed that Ej has the same value of 0.85 for all regions and the rate constants k2,j and k3,j could be determined for fairly large regions.…”
Section: General Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, x ¼ À F/PS and a ¼ À F r /PS are substituted into equation (6). As FEF r , the linear approximation (equation (6)) makes sense.…”
Section: Aðtþ Dt ð2þmentioning
confidence: 99%
“…In the brains of rats under pentobarbital anesthesia 19 and in normal patients, 20 Matsuda et al also demonstrated rCBF values determined with [ " r e ] HM-PAO significantly lower than those obtained with radiolabeled microspheres. These data also suggest that [""TcJHM-PAO acts like a chemical microsphere over only a limited range of blood flows.…”
mentioning
confidence: 99%